2013
DOI: 10.1371/journal.pone.0064450
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Follow-Up of Responses to Treatment with Benznidazol in Amazon: A Cohort Study of Acute Chagas Disease

Abstract: A total of 179 individuals with acute Chagas disease mainly transmitted by oral source, from Pará and Amapá State, Amazonian, Brazil were included during the period from 1988 to 2005. Blood samples were used to survey peripheral blood for T. cruzi hemoparasites by quantitative buffy coat (QBC), indirect xenodiagnosis, blood culture and serology to detection of total IgM and anti-T. cruzi IgG antibodies by indirect immunofluorescence assay (IFA) and indirect hemagglutination assay (HA). All assays were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
18

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 17 publications
1
35
0
18
Order By: Relevance
“…In contrast, these tests are most recommended for use in the acute phase of the disease due to the high parasitemia [33]. In this study, blood cultures showed a very low sensitivity in patients with a latent asymptomatic phase.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, these tests are most recommended for use in the acute phase of the disease due to the high parasitemia [33]. In this study, blood cultures showed a very low sensitivity in patients with a latent asymptomatic phase.…”
Section: Discussionmentioning
confidence: 81%
“…A serologic response to treatment was found in 26.3% of patients, most evident four years after treatment; 2.7% developed a chronic mild-tomoderate cardiomyopathy; and 73.7% had persistently reactive serology, although with a significant decrease in the levels of antibodies (156) .…”
Section: Specific Treatmentmentioning
confidence: 98%
“…The World Health Organization (WHO) estimates that approximately 6-7 million people are infected worldwide, mostly in Latin America (14) .Recent estimates for the 21 Latin American countries, based on data from 2010, showed that 5,742,167 people were infected by Trypanosoma cruzi, of which 3,581,423 (62.4%) were living in the countries of the Southern Cone Initiative against Chagas disease, especially Argentina (1,505,235), Brazil (1,156,821), Mexico (876,458), and Bolivia (607,186) (5) . However, these data differ from the estimates of other research groups using other methods to define T. cruzi infection in many countries; this hinders accurate establishment of the prevalence of Chagas disease in the Americas.…”
Section: General Aspects Of Chagas Disease Epidemiology With Specifimentioning
confidence: 99%
“…Gaining knowledge about the biological properties of the TcI lineage, which certainly plays an important role in the CD pathogenesis and response to the specific chemotherapy in the Amazon region, represents a challenge for future research [39-41]. …”
Section: Discussionmentioning
confidence: 99%